Phylogenetic and genetic linkage between novel atypical dual-specificity phosphatases from non-metazoan organisms - Romá-Mateo, C.; Sacristán-Reviriego, A.; Beresford, N.; Caparrós-Martín, Jose; Culiáñez-Macià, F.; Martín, H.; Molina, M.; Tabernero, L.; Pulido, R. (2011)
Dual-specificity phosphatases (DSPs) constitute a large protein tyrosine phosphatase (PTP) family, with examples in distant evolutive phyla. PFA-DSPs (Plant and Fungi Atypical DSPs) are a group of atypical DSPs present in plants, fungi, kinetoplastids, and slime molds, the members of which share structural similarity with atypical- and lipid phosphatase DSPs from mammals. The analysis of the PFA-DSPs from the plant Arabidopsis thaliana (AtPFA-DSPs) showed differential tissue mRNA expression, substrate specificity, and catalytic activity for these proteins, suggesting different functional roles among plant PFA-DSPs. Bioinformatic analysis revealed the existence of novel PFA-DSP-related proteins in fungi (Oca1, Oca2, Oca4 and Oca6 in Saccharomyces cerevisiae) and protozoa, which were segregated from plant PFA-DSPs. The closest yeast homolog for these proteins was the PFA-DSP from S. cerevisiae ScPFA-DSP1/Siw14/Oca3. Oca1, Oca2, Siw14/Oca3, Oca4, and Oca6 were involved in the yeast response to caffeine and rapamycin stresses. Siw14/Oca3 was an active phosphatase in vitro, whereas no phosphatase activity could be detected for Oca1. Remarkably, overexpression of Siw14/Oca3 suppressed the caffeine sensitivity of oca1, oca2, oca4, and oca6 deleted strains, indicating a genetic linkage and suggesting a functional relationship for these proteins. Functional studies on mutations targeting putative catalytic residues from the A. thaliana AtPFA-DSP1/At1g05000 protein indicated the absence of canonical amino acids acting as the general acid/base in the phosphor-ester hydrolysis, which suggests a specific mechanism of reaction for PFA-DSPs and related enzymes. Our studies demonstrate the existence of novel phosphatase protein families in fungi and protozoa, with active and inactive enzymes linked in common signaling pathways. This illustrates the catalytic and functional complexity of the expanding family of atypical dual-specificity phosphatases in non-metazoans, including parasite organisms responsible for infectious human diseases. © Springer-Verlag 2011.